2021
DOI: 10.3390/jcm10163743
|View full text |Cite
|
Sign up to set email alerts
|

Criterion-Related Validity of Field-Based Fitness Tests in Adults: A Systematic Review

Abstract: We comprehensively assessed the criterion-related validity of existing field-based fitness tests used to indicate adult health (19–64 years, with no known pathologies). The medical electronic databases MEDLINE (via PubMed) and Web of Science (all databases) were screened for studies published up to July 2020. Each original study’s methodological quality was classified as high, low and very low, according to the number of participants, the description of the study population, statistical analysis and systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 104 publications
(234 reference statements)
0
25
0
Order By: Relevance
“…A recent meta-analysis concluded that the shuttle run test provided a useful alternative for estimating CRF with the performance score on the 20m SRT being a strong estimate of CRF in adults [8]. The latter study was reinforced by Castro-Pinero, et al [9] who provided ('strong') evidence suggesting the 20mSRT was valid for estimating cardiorespiratory fitness in healthy adults aged 19-64 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis concluded that the shuttle run test provided a useful alternative for estimating CRF with the performance score on the 20m SRT being a strong estimate of CRF in adults [8]. The latter study was reinforced by Castro-Pinero, et al [9] who provided ('strong') evidence suggesting the 20mSRT was valid for estimating cardiorespiratory fitness in healthy adults aged 19-64 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Poor reliability reduces validity of tests and usefulness of results. Exercise professionals should select tests with easy-to-follow procedures, observation, and performance criteria that match their skill proficiency and competence (3,30).…”
Section: Instrument Qualitiesmentioning
confidence: 99%
“…Reliability refers to whether test results are repeatable by the same or between separate administrators (30). Following standardized protocols and procedures, giving consistent client instructions, conducting routine calibration of equipment, and developing test administrator technical skill(s) proficiency can affect the quality, accuracy, and usefulness of results for prescribing clients' exercise programs.…”
Section: Instrument Qualitiesmentioning
confidence: 99%
“…In addition to the 2 MR , several other field tests such as the 12-mile run, the 3000-m run, the 2400-m run, and the 1-mile run are used for CRF evaluation of military personnel 3,9 . Later tests are usually conducted outdoors and were found to have questionable validity ranging from low to high 10,11 . Therefore, weather, climate, and terrain can influence the results and may limit the maximum and reliable performance.…”
Section: Trial Registration Number: Nct05218798mentioning
confidence: 99%